(untitled) (Journal of Educational Sciences, 2019)
The category of an archetype is a synthetic category, which lies in the general semantic space of philosophy, cultural studies, psychology, literary criticism and linguistics. Forming the students’ under- standing about an archetype as a universal category contributes to the enlargement of their intellectual horizon. The article suggests various methods and methodical tools for analyzing the novel “The Bitter Line” by I.Shukhov and autobiographical trilogy “The Presnovsky Pages”. For example, at the stage of verticalization of the context, students study the historical facts reflected in the novel “Bitter Line” by Shukhov. Another important methodological aspect of studying the archetype “house” in the novel by I. Shukhov is the compilation of a culturological portrait of ethnic groups. The study of individual cultural concepts - such as the horse or wormwood - allows students to decipher the plot elements of the work. The compilation by students of an axiological map of an ethnos, in the center of which is the “house” archetype, is necessary for a deep understanding of this category. In the process of studying the archetype “house” in the novels of I. Shukhov, other methodological techniques can be applied, including various types of commentary. The analysis of stylistic units will also prepare students for understanding the poetics of Shukhov on the example of the ing the classes at the university is based on a detailed analysis of the archetype of the house. The article proves that during the analysis of the “house” archetype in the works of I. Shukhov, students develop perceptions of tolerance, respect for different peoples and their cultures is formed. Key words: archetype, the archetype “house”, I. Shukhov, novel “The Bitter line”, trilogy “The Pres- novsky pages”, context verticalization, axiological map of ethnos.